1999
DOI: 10.1121/1.426724
|View full text |Cite|
|
Sign up to set email alerts
|

Pitch accent in spoken-word recognition in Japanese

Abstract: Three experiments addressed the question of whether pitch-accent information may be exploited in the process of recognizing spoken words in Tokyo Japanese. In a two-choice classification task, listeners judged from which of two words, differing in accentual structure, isolated syllables had been extracted ͑e.g., ka from baka HL or gaka LH͒; most judgments were correct, and listeners' decisions were correlated with the fundamental frequency characteristics of the syllables. In a gating experiment, listeners hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
84
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 94 publications
(101 citation statements)
references
References 26 publications
7
84
0
Order By: Relevance
“…For each of the extracted syllables, the total syllable duration and the duration of the vowel were measured, plus, across the voiced portions of the signal only, "ve f measures (minimum f ; maximum f ; f range; mean f ; standard deviation of f ) and two amplitude measures (mean rms amplitude; standard deviation of rms amplitude). All these acoustic data can be found in Cutler & Otake (1999).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…For each of the extracted syllables, the total syllable duration and the duration of the vowel were measured, plus, across the voiced portions of the signal only, "ve f measures (minimum f ; maximum f ; f range; mean f ; standard deviation of f ) and two amplitude measures (mean rms amplitude; standard deviation of rms amplitude). All these acoustic data can be found in Cutler & Otake (1999).…”
Section: Methodsmentioning
confidence: 99%
“…For the original subject group, Cutler & Otake (1999) reported that subjects were signi"cantly more likely to decide that a syllable was H when it had high minimum f , high maximum f , high mean f , and high mean amplitude, and were signi"cantly less likely to decide that a syllable was H when it had a large f range or when it had a large f standard deviation. These four positive and two negative correlations also appeared, across the full set of 96 tokens, in the responses of each of the two new subject groups.…”
Section: Suprasegmental Structure In Non-native Dialectmentioning
confidence: 99%
See 2 more Smart Citations
“…In Japanese [39], it was found that pitch movement can help in the selection of word candidates. In Swedish, syllables in words are contrasted through lexical stress.…”
Section: Discussion and Remarksmentioning
confidence: 99%